Nata de coco patches supplemented with herbal extracts for the inhibition of acne-inducing bacteria - Jongsareejit, Boonsri; Suwannarat, Kedsarin; Moosiri, Panicha; Yooyongsatit, Surasak (Journal of Medicine and Health Sciences, 2025)
This study examines herbal extracts as an alternative acne treatment to reduce antibiotic use, which may contribute to drug resistance, by evaluating their efficacy in inhibiting acne-related bacteria, including Staphylococcus aureus, Staphylococcus epidermidis, and Cutibacterium spp. To determine the most effective extracts and develop them into acne patches that are composed of Nata de coco combined with herbal extracts and compare the efficacy of the most effective extracts in inhibiting acne-causing microbes with commercial acne patches by disc diffusion and dilution methods. The result demonstrated that the mangosteen pericarp extract in ethanol solvent exhibited the greatest effectiveness in suppressing the growth of all three bacterial strains, with inhibition zone diameters measuring 21.33±1.15, 18.00±3.46, and 14.67±1.15 millimeters, respectively. Lower inhibition levels were seen in the mangosteen pericarp extract in DMSO and the lakoocha extract in both ethanol and DMSO. On the other hand, the extracts of turmeric and tanaka showed minimal inhibition, while the extracts using distilled water as a solvent showed no inhibition. The minimum inhibitory concentration (MIC) of the mangosteen pericarp extract in distilled water was determined to be 3.6×10-7, 3.6×10-7, and 3.6×10-9 milligrams per milliliter (mg/ml), respectively, for bacterial inhibition. The inhibitory concentrations in the ethanol solvent were 3.6x10-9, 3.6x10-8, and 3.6x10-8 mg/ml, respectively. The lakoocha extract exhibited comparable benefits but necessitated greater doses. Furthermore, the turmeric and tanaka extracts combined with distilled water failed to demonstrate the minimum inhibitory concentration (MIC). The experimental results demonstrated that the anti-acne patches developed from Nata de coco incorporated with mangosteen pericarp and lakoocha extracts exhibited superior antibacterial activity against all three tested bacterial strains compared to the commercial anti-acne patches, which showed no inhibitory effect. These findings suggest that the anti-acne patches made with Nata de coco and herbal extracts from mangosteen pericarp and lakoocha could be developed further as a strong acne treatment.